Integrating new approaches for clinical development: translational research and relative effectiveness. (January 2012) - Lehner, Jean-Pierre; Epstein, Robert S; Salimi, Tehseen
Translational research and relative effectiveness are being incorporated into drug development programs to meet the demands for more robust evidence generation to support the value of new therapies. Translational research includes translating basic research into clinical practice, controlled clinical trials into potential clinical implications, evidence-based guidelines into routine clinical practice and standard practices into population health. These research concepts link with real-world outcomes, and feed into each other to improve the efficiency of research. Translational research can run into road blocks in terms of conveying the added or comparative value of research or during adoption into clinical practice. Understanding these roadblocks and developing solutions are important for success. Comparative effectiveness research can be a useful research technique to accomplish many translational medicine goals. These studies generally include heterogeneous patient populations and evaluate outcomes of relevance to payers and health technology assessors. Comparative effectiveness research can be used in drug development; different methodologies may be useful in different phases. In this article, suggestions and examples of successful use of comparative effectiveness studies are provided. Translational research and comparative effectiveness research, although clearly independent concepts, can provide a focused approach to drug development, resulting in products entering the market that bring added benefit to patients and the healthcare system overall.